STUDI KOMPARATIF PANDANGAN IMAM AL-GHOZALI DAN IBNU HAZM TENTANG ‘AZL - Hamdani Romdon; Ibnu Jazari; Humaidi Kurniawati (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2021)
Islam is the religion that the majority of the population embraces the state of Indonesia, not only religion of worship, but also as a social system. Islamic law is very global in meet human needs and concerns. Islam too consider family planning issues factually and affectionate and has sponsored human plans invarious individual and social affairs, including the birth plana child.Al-Ghazali who adheres to the Islamic teachings of the Shafi'iyah madhhab in his book Ihya' 'Ulumuddin mentions that 'azl can be done without the consent of the wife. In addition to basing his argument on the hadith of the Prophet, Imam Al-Ghazali also discussed this issue from various aspects, especially from the biological aspect and the economic aspect.Unlike the case with Imam Ibn Hazm, most of his opinions are contrary to the Ulama'. Ibn Hazm who adheres to the Islamic teachings of the Zahiri school strongly opposes the implementation of the practice of 'azl on the grounds of